UAV-BS Operation Plan Using Reinforcement Learning for Unified Communication and Positioning in GPS-Denied Environment - Haile, Gebreselassie; Lim, Jaesung (IEICE Transactions on Communications, 2024)
An unmanned aerial vehicle (UAV) can be used for wireless communication and localization, among many other things. When terrestrial networks are either damaged or non-existent, and the area is GPS-denied, the UAV can be quickly deployed to provide communication and localization services to ground terminals in a specific target area. In this study, we propose an UAV operation model for unified communication and localization using reinforcement learning (UCL-RL) in a suburban environment which has no cellular communication and GPS connectivity. First, the UAV flies to the target area, moves in a circular fashion with a constant turning radius and sends navigation signals from different positions to the ground terminals. This provides a dynamic environment that includes the turning radius, the navigation signal transmission points, and the height of the unmanned aerial vehicle as well as the location of the ground terminals. The proposed model applies a reinforcement learning algorithm where the UAV continuously interacts with the environment and learns the optimal height that provides the best communication and localization services to the ground terminals. To evaluate the terminal position accuracy, position dilution of precision (PDOP) is measured, whereas the maximum allowable path loss (MAPL) is measured to evaluate the communication service. The simulation result shows that the proposed model improves the localization of the ground terminals while guaranteeing the communication service.
Keywords: Aerial vehicle; Communication service; Ground terminals; Localisation; Localization services; Position dilution of precision; Reinforcement learnings; Turning radius; Unified communications; Unmanned aerial vehicle; communication; localization; PDOP; reinforcement learning; unmanned aerial vehicle